Manfaat Penggunaan Media Gambar dalam Proses Pembelajaran Menulis Teks Deskripsi Siswa SMP IT Darussalam Tanon - Nila Fitri Faidzah; Suparmin; Wahyu Dini Septiari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to ascertain how picture media is used in the process of learning to write descriptive texts and whether or not it may help students in Class VII SMP IT Darussalam Tanon become better writers of descriptive texts. This study employs a descriptive qualitative methodology and gathers data through teacher and student interviews, classroom observations, and examination of students' writing both before and after the images are applied. Data triangulation—that is, comparing the findings of observations, interviews, and document analysis—was done in order to preserve the validity of the data. In order to achieve data accuracy, the triangulation technique employed was source triangulation, using data sources from students, teachers, and student writing. According to the findings of 32 student interviews, 29 students (90.63%) said that utilizing image media greatly aided them in writing descriptive text, whereas 3 students (9.57%) acknowledged that they still struggled with writing descriptive text even with the use of image media. These findings show that, even if some students still struggle, using picture media in descriptive text writing is a highly effective way to help students become better descriptive text writers. It has also been successful in raising kids' interest in writing through the use of picture media. Interviews with teachers indicate that this approach not only boosts writing abilities but also students' enthusiasm in studying. Students' interviews demonstrate that photos help pupils visualize and characterize the environment they observe.